How "monetization" really works: Examples from nations' policy responses to COVID-19 - Jesus Felipe; Scott Fullwiler; Gemma Estrada; Maria Hanna Jaber; Mary Ann Magadia; Remrick Patagan (Asian Development Bank (ADB), 2020)
The severe economic downturn caused by the coronavirus disease (COVID-19) pandemic has forced governments worldwide to increase spending while tax revenues simultaneously collapsed. Concurrent with this, central banks in several of these countries are financing a significant percent of their direct income support through direct lending or purchases of government bonds in primary and/or secondary markets. Many oppose this for their alleged negative consequences on the economy, inflation in particular. This paper describes the actual workings of what most people (including many economists) often call monetization of government debt and its major implication, namely, that it leads to printing money and, consequently, to inflation. We show that the reality is very different: once one knows how modern central banks manage monetary policy (i.e., through a corridor interest rate targeting system), and how they coordinate their daily operations with their treasuries, monetization does not occur as it is often described, and it is not nearly as dangerous as its critics argue (and not as useful as its supporters claim). The examples of the People's Republic of China, the Philippines, Singapore, and the United States clarify this.
Keywords: E42; E52; E58; 330; central bank; corridor system; inflation; monetization; printing money